Implications of emergent risk for application of risk transfer mechanisms by local governments in Queensland. Issue 96 (June 2019) - Edwards, Ian; Nalau, Johanna; Burton, Donovan; Mackey, Brendan
Highlights: Presents a typology of emergent risk that highlights the iterative and inter-related nature of climate change risk, and propensity for impacts, such as legal action and reduced debt access, to emerge subsequent to, yet far removed from, initial physical impacts. Highlights current practice and gaps in local government risk management concerning emergent risk. Highlights the potential and need for local government to consider, the application of risk transfer mechanisms such as catastrophe bonds in the face of historical and conceivable climate change-perpetuated reduced access to, and increased cost of, traditional mechanisms such as insurance. Provides insight into barriers and enablers to local government agencies gaining an appreciation of the potential application of alternative risk transfer mechanisms. Abstract: Insurance represents an integral part of local government risk management strategy. As climate change progresses, increased loss and risk related to extreme weather events such as tropical cyclones, could motivate insurers to withdraw from certain markets. In some regions, such a withdrawal represents an emergent risk that, when coupled with increasing populations and other climate change impacts, could leave local governments and ratepayers particularly vulnerable. This paper investigates such a scenario and its ramifications in the context of a region particularly vulnerable to climate change, through an exploration of the degree that consideration of emergent risks, such as loss of insurance, and the potential application of insurance alternatives influence Queensland local government risk management. The study finds little appreciation amongst government officials of emergent risk implicit in extreme weather events such as cyclones, little understanding of the nuances of risk transfer mechanisms beyond familiar traditional insurance and disaster funding mechanisms, and by default, a lack of appreciation of the relationship between the two. A lack of resource and leadership with respect to emergent risk, and an absence of dialogue between insurance brokers and local government concerning climate change risk arise as the main reasons for this result. This research is significant because it challenges current local government risk management practice through an exploration of the risks inherent in the process itself. This has potential social, economic and ecological ramifications in drawing attention to aspects of possible "uninsurability" and prospects of alleviation thereto. Further research is recommended to consider the insurance industry's part in this study's findings in order to inform current industry practice and thinking and further enlighten the causes of local government disengagement in this critical area.